Polymer solar cells - Singh, Ram Prakash; Kushwaha, Omkar Singh (Journal of Materials Education, 2013)
It is a well known fact that the amount of solar energy impinging on the earth's surface in one hour is higher than the worldwide energy demand per year. Solar energy is the ultimate renewable zero emission energy source. Solar energy technology which is dominated by the crystalline silicon has not found widespread acceptance due to size, weight, aesthetics, cost and installation of solar panels. On the other hand, polymer solar cells being light weight, inexpensive, colorful and capable to be fabricated into large area flexible devices by roll to roll processes, portend potential for large scale non-grid and grid power generation applications. Polymer solar cells would reduce the need for petroleum and natural gas for power generation; therefore, the use of cells would slow down the disappearance of non-renewable resources and promote sustainability. In spite of these facts, polymer solar cells are not covered in current curricula and textbooks of Materials Science and Engineering. The present article intends to provide the remedy to this situation and exhaustively discusses materials, mechanisms and applications in the development of highly efficient polymer solar cells (PSCs).
Keywords: Bulk heterojunction polymer solar cells; Electron acceptors; Electron donors; Inverted and Tandem solar cells; Roll to roll processing; Solar cell efficiency

Polymer solar cells: an overview - Singh, Ram Prakash; Kushwaha, Omkar Singh (Macromolecular Symposia, 2013)
Polymer Solar cells being flexible, light weight, inexpensive, colorful and large area devices, portend potential for large scale grid power generation. The first major breakthrough in organic solar cell performance came in 1986 when Tang discovered that much higher efficiencies about 1% can be attained when electron donor (D) and electron acceptor (A) are brought together in one cell. With the discovery of photo induced electron transfer from a conjugated polymer to fullerene molecules in 1992, the bulk heterojunction (BHJ) polymer solar cell has become the most successful device structure developed in the field till date. Poly(3-hexyl thiophene) (P3HT) has been the subject of intensive investigations upto 2008 yielding power conversion efficiencies (PCEs) around 5-6%. OPV technology has grown during the past decade with cell efficiencies quadrupling. As alternative route of higher performance, two or more single cells can be combined in tandem structure. The most efficient tandem organic solar cell reported by Yang Yang's group has 8.62% power conversion efficiency (PCE) which has been further improved with an NREL - certified PCE of 10.6%. An overview of the above will be presented in this paper.
Keywords: bulk heterojunction; electron acceptor; electron donor; fullerenes; polymer solar cells

Effect of additives on formation and decomposition kinetics of methane clathrate hydrates: application in energy storage and transportation - Kumar, Asheesh; Kushwaha, Omkar Singh; Rangsunvigit, Pramoch; Linga, Praveen; Kumar, Rajnish (Canadian Journal of Chemical Engineering, 2016)
Methane gas storage and transportation via clathrate hydrates is proposed to be a potential solution for large-scale energy storage. In this work, we study the formation and decomposition kinetics of methane hydrates (MH) in a laboratory-scale unstirred crystallizer. The present investigation demonstrates comparative studies of hydrate formation and dissociation kinetics in the presence of tetrahydrofuran (55.6 and 27.8mmol/mol, 5.56 and 2.78mol% THF) and sodium dodecyl sulphate (1mg/g, 0.1wt% SDS). Moreover, the storage capacity and hydrate formation kinetics in both the systems are discussed. In a recent work, enhanced methane hydrate growth in the presence of THF at close to atmospheric conditions was demonstrated. The emphasis of the current work is to study the stability of hydrates to understand dissociation kinetics by measuring the rate of hydrate decomposition at different temperatures. Hydrate stability measurements were performed at -8, -3, 2, 10, and 20 degrees C to study the decomposition rates of MH and self-preservation in presence of the two additives THF and SDS.

Biosurfactant surfactin as a kinetic promoter for methane hydrate formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Pradhan, Darshan; Naik, Rajesh; Zare, Kirti; Mawlankar, Rahul R.; Dastager, Syed Gulam; Kushwaha, Omkar Singh; Kumar, Rajnish (Energy Procedia, 2017)
In the present study, the effect of the biosurfactant Surfactin on methane hydrate formation kinetics was studied. Initially, several marine derived species were screened for the presence of Surfactin. The polymerase chain reaction technique was used as the preliminary screening step for Surfactin which was then followed up by a couple of different assays to provide conclusive evidence of the same. Based on these tests, the D-9 bacterial strain was identified as a producer of Surfactin. Once the presence of Surfactin had been proven, its effect on methane hydrate formation kinetics was investigated upon by carrying out hydrate formation experiments in a stirred tank reactor. The cell free supernatant containing Surfactin was itself used as the hydrate forming solution without any further processing. It was found that the presence of Surfactin in the system greatly enhances hydrate formation kinetics as compared to pure water. In fact the kinetics in presence of Surfactin also surpassed that obtained with 1 wt% SDS, the most commonly used synthetic kinetic hydrate promoter. This basic study can pave the way for more sophisticated research on the use of biosurfactants as kinetic promoters with a view on rapid methane hydrate formation kinetics for applications such as methane separation, storage and transport.

Effects of micellization on growth kinetics of methane hydrate - Bhattacharjee, Gaurav; Kushwaha, Omkar Singh; Kumar, Asheesh; Khan, Muzammil Yusuf; Patel, Jay Narayan; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2017)
Surfactants are Specific functional materials, that form various types of self-assemblies and affect local water ordering alongside solution properties. Such surface active agents are used extensively in gas hydrate based applications as kinetic hydrate promoters. To understand the effect of surfactant micelles on hydrate formation kinetics, a novel surfactant system capable of producing micelles at hydrate forming temperature was developed. The presence of surfactant micelles in this new system (a combination of anionic surfactant SDS and zwitterionic surfactant CAPB) was determined through DLS measurements. Pure methane and a coal bed methane mixture were individually used to assess the efficacy of the surfactant mixture for hydrate formation. This study conclusively proves for the first time that the presence of surfactant micelles enhances hydrate formation kinetics. The findings reported here can contribute significantly toward improving the utility of surfactants in gas hydrate based technological applications such as gas separation and methane storage.

Molecular dynamics simulation and experimental study on the growth of methane hydrate in presence of methanol and sodium chloride - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Energy Procedia, 2017)
The plugging of processing and transportation lines by gas hydrate formation is a challenging problem for safe exploitation of oil and gas. The existence of water soluble third component (like methanol and sodium chloride) in the aqueous phase influence the gas hydrate formation thermodynamically also possibly affects the kinetics of hydrate growth. Inorganic salt and organic molecule (alcohols) at high concentration in the aqueous phase have been used as thermodynamic inhibitors to effectively prevent the hydrate formation. This study utilizes molecular dynamics as well as an experimental method to investigate the mechanism of the hydrate formation and the effect of additives. The MD simulation showed that at moderate temperature and pressure, a low concentration (1 wt %) of methanol and NaCl enhances methane hydrate growth kinetics. Significant numbers of methanol molecules were observed inside the gas hydrate cages whereas Na⁺/Cl⁻ ions leach out during hydrate formation.

Macro and molecular level insights on gas hydrate growth in the presence of hofmeister salts - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2020)
The effect of few monovalent salts (NaCl, NH4Cl, and GdmCl) as additives, according to the Hofrneister series on the growth of methane gas hydrates, has been studied using experiments as well as molecular dynamics (MD) simulation. Further, the Hofmeister effects on hydrate crystallization have been correlated with the methanol as an additive, which is a known thermodynamic hydrate inhibitor for hydrate growth. One of the previous studies (discussed later in this article) available in the literature concludes that methane hydrate formation from ice might show enhanced kinetics in the presence of salts; this behavior is contrary to the general usage of such salts as hydrate inhibitors. This conclusion may not necessarily be true for experiments done with liquid water, and therefore, this work explores the behavior of these salts in a lab-scale setup. In addition, current work reports detailed MD simulation studies to gain insight into the mechanism of hydrate formation in the presence of Hofmeister series salts at two different concentrations of 1 and 10 wt % in water and compare the results with hydrate formation in the methanol-water system. Our study suggests that the presence of these additives at low concentrations (1 wt %) does enhance the hydrate growth kinetics. However, at higher concentrations (10 wt %), inhibition by these additives persisted, and prolonged nucleation, as well as retarded growth, was observed.